Improved inhibition of telomerase by short twisted intercalating nucleic acids under molecular crowding conditions - Agarwal, Tani; Pradhan, Devranjan; Geci, Imrich; El-Madani, Amro M.; Petersen, Michael; Pedersen, Erik B.; Maiti, Souvik (Nucleic Acid Therapeutics, 2012)
Human telomeric DNA has the ability to fold into a 4-stranded G-quadruplex structure. Several G-quadruplex ligands are known to stabilize the structure and thereby inhibit telomerase activity. Such ligands have demonstrated efficient telomerase inhibition in dilute conditions, but under molecular crowding conditions mimicking physiological milieu, stabilization of the telomeric G-quadruplex is often lost. We attempted to demonstrate the enhanced G-quadruplex stabilizing ability under molecular conditions by using twisted intercalating nucleic acids (TINA)-modified oligonucleotides. We have shown using circular dichroism and ultraviolet spectroscopic methods that these TINA-modified short oligonucleotides function as G-quadruplex, inducing agents and participate in the formation of stabilized 3:1 G-quadruplex with the human telomeric oligonucleotide. Using enzyme-linked immunosorbent assay-based telomerase repeat amplification assay (TRAP) assay as well as nondenaturing polyacrylamide gel electrophoresis-based TRAP, we demonstrate remarkable enhancement in their anti-telomerase activity even under molecular crowding conditions. This is the first time in which a G-quadruplex stabilizing agent has demonstrated enhanced activity even under molecular crowding conditions.

In the sense of transcription regulation by G-quadruplexes: asymmetric effects in sense and antisense strands - Agarwal, Tani; Roy, Saumya; Kumar, Santosh; Chakraborty, Tushar Kanti; Maiti, Souvik (Biochemistry, 2014)
G-Quadruplexes occupy important regulatory regions in the genome. DNA G-quadruplexes in the promoter regions and RNA quadruplexes in the UTRs (untranslated regions) have been individually studied and variously implicated at different regulatory levels of gene expression. However, the formation of G-quadruplexes in the sense and antisense strands and their corresponding roles in gene regulation have not been studied in much detail. In the present study, we have elucidated the effect of strand asymmetry in this context. Using biophysical methods, we have demonstrated the formation of stable G-quadruplex structure in vitro using CD and UV melting. Additionally, ITC was employed to demonstrate that a previously reported selective G-quadruplex ligand was able to bind and stabilize the G-quadruplex in the present sequence. Further, we have shown using reporter constructs that although the DNA G-quadruplex in either strand can reduce translation efficiency, transcriptional regulation differs when G-quadruplex is present in the sense or antisense strand. We demonstrate that the G-quadruplex motif in the antisense strand substantially inhibits transcription, while when in the sense strand, it does not affect transcription, although it does ultimately reduce translation. Further, it is also shown that the G-quadruplex stabilizing ligand can enhance this asymmetric transcription regulation as a result of the increased stabilization of the G-quadruplex.

Influence of ionic liquids on thermodynamics of small molecule DNA interaction: the binding of ethidium bromide to calf thymus DNA - Mishra, Arpit; Ekka, Mary Krishna; Maiti, Souvik (Journal of Physical Chemistry B, 2016)
Ionic liquids (ILs) are salts with poor ionic coordination, resultantly remaining in liquid state below 100 degrees C and some may retain liquid state even at room temperature. ILs are known to provide a conducive environment for many biological enzymatic reactions, but their interaction with biomacromolecules are poorly understood. In the present study, we investigate the effect of various ionic liquids on DNA small molecule interaction using calf thymus DNA (ctDNA) ethidium bromide (EB) as a model system. The effect of various ionic liquids on these interactions is studied by an array of techniques such as circular dichroism (CD), UV melting, fluorescence exclusion and isothermal titration calorimetry. Interestingly, we observed that presence of IL increased the stability of ctDNA without altering its structure. The binding affinities Kbs for EB binding to ctDNA in the presence of 300 mM ILs are about half order of magnitude smaller than the Kbs in absence of ILs and correspond to a less favorable free energy. We noted that, when adjusted to corresponding buffer condition, the unfavorable shift in AG of ctDNA-EB interaction is attributed to decreased entropy in the case of ILs, whereas the same effect by NaCI was due to increased enthalpy.

Inhibition of miR-21 by 3 `/5 `-serinyl-capped 2 `-O-Methyl RNA Interspersed with 2 `-O-(2-Amino-3-Methoxypropyl) uridine units - Nahar, Smita; Kotikam, Venubabu; Kumar, Vaijayanti A.; Maiti, Souvik (Nucleic Acid Therapeutics, 2016)
miRNAs are highly conserved class of small ncRNAs whose involvement in human pathophysiologies is extensively investigated. MiR-21 is a well established oncogenic miRNA whose deregulation plays a significant role in onset and progression of cancer. The need of novel approaches to downregulate miR-21 is rapidly expanding. Potent inhibition of miR-21 is achieved by chemically modified 2-O-methyl RNA oligonucleotide. The serinol capping at 3 and 5ends and the interspersed 2-O-(R-2-amino-3-methoxypropyl) uridine units enhance the nuclease resistance and efficacy of 2-O-methyl RNA for the inhibition of miR-21. This represents a simple and novel modification for developing oligonucleotide-based therapeutics.
Keywords: antagomirs; cancer; microRNA; noncoding RNA; oligonucleotides

Identification of G-quadruplex structures in MALAT1 lncRNA that interact with nucleolin and nucleophosmin - Ghosh, Arpita; Pandey, Satya Prakash; Joshi, Dheeraj Chandra; Rana, Priya; Ansari, Asgar Hussain; Sundar, Jennifer Seematti; Singh, Praveen; Khan, Yasmeen; Ekka, Mary Krishna; Chakraborty, Debojyoti; Maiti, Souvik (Nucleic Acids Research, 2023)
Nuclear-retained long non-coding RNAs (lncRNAs) including MALAT1 have emerged as critical regulators of many molecular processes including transcription, alternative splicing and chromatin organization. Here, we report the presence of three conserved and thermodynamically stable RNA G-quadruplexes (rG4s) located in the 3 & PRIME; region of MALAT1. Using rG4 domain-specific RNA pull-down followed by mass spectrometry and RNA immunoprecipitation, we demonstrated that the MALAT1 rG4 structures are specifically bound by two nucleolar proteins, Nucleolin (NCL) and Nucleophosmin (NPM). Using imaging, we found that the MALAT1 rG4s facilitate the localization of both NCL and NPM to nuclear speckles, and specific G-to-A mutations that disrupt the rG4 structures compromised the localization of both NCL and NPM in speckles. In vitro biophysical studies established that a truncated version of NCL (& UDelta;NCL) binds tightly to all three rG4s. Overall, our study revealed new rG4s within MALAT1, established that they are specifically recognized by NCL and NPM, and showed that disrupting the rG4s abolished localization of these proteins to nuclear speckles